Determinants of childhood pneumonia: a retrospective hospital-based analysis - Lu, Yan (Frontiers in Medicine, 2025)
BackgroundChildhood pneumonia remains a leading cause of morbidity and mortality in low- and middle-income countries, driven by a complex interplay of socioeconomic, environmental, and modifiable risk factors.ObjectiveTo investigate determinants of pneumonia among children aged 2–59 months in resource-limited settings, with a focus on healthcare, nutritional, and environmental factors.MethodsA retrospective hospital-based case–control study was conducted using medical records of children aged 2–59 months. Cases were physician-diagnosed pneumonia based on WHO IMCI criteria, while controls were children without respiratory illness presenting for unrelated conditions. Data on demographics, household exposures, immunization, nutrition, and feeding practices were extracted using a standardized form.ResultsMultivariable analysis identified significant risk factors: use of unclean cooking fuel (AOR = 2.01; 95% CI: 1.25–3.23), incomplete immunization (AOR = 2.78; 95% CI: 1.24–6.20), and lack of exclusive breastfeeding for 6 months (AOR = 2.10; 95% CI: 1.32–3.34). Maternal age ≥25 years was also associated with increased risk (AOR = 2.04; 95% CI: 1.26–3.31). Malnutrition showed an unexpected protective effect (AOR = 0.13; 95% CI: 0.08–0.23), while zinc supplementation showed a moderate effect (AOR = 1.63; 95% CI: 1.01–2.64). No significant associations were observed for HIV status, vitamin A supplementation, smoking exposure, child age, sex, or household crowding.ConclusionChildhood pneumonia in under-five children is strongly influenced by modifiable factors, particularly breastfeeding practices, immunization coverage, nutritional status, and household energy sources. Targeted interventions addressing these determinants may substantially reduce the burden of pneumonia in resource-limited settings.